Is there an association between osteoporosis and uric acid? - N. V. Toroptsova; O. V. Dobrovolskaya; M. V. Kozyreva; N. V. Demin (Научно-практическая ревматология, 2024)
The aim – to study the association between serum uric acid (SUA) level, bone mineral density (BMD) and osteoporosis (OP) in postmenopausal women.Materials and methods. 394 postmenopausal women were examined (median age – 62 [56; 68] years). Examination and anthropometric measurements, a biochemical blood test, including level of SUA, dual-energy X-ray absorptiometry of the lumbar spine (L1–L4), femoral neck (FN) and total hip (TH) were carried out.Results. In women with OP, the level of SUA and the frequency of hyperuricemia were lower than in those without OP (p=0.005 and p=0.019, respectively). SUA was weakly positively correlated with BMD in L1–L4 (r=0.20; p<0.001), FN (r=0.12; p=0.021) and TH (r=0.17; p=0.001). A weak negative correlation was found between the level of SUA and the presence of OP (r=–0.13; p=0.008). Multiple logistic regression analysis showed that the independent factors associated with OP in postmenopausal women were age (odds ratio (OR) – 1.06 (95% confidence interval (95% CI): 1.02–1.10); p=0.003) and body mass index (OR=0.83 (95% CI: 0.77–0.89); p<0.001). There was no significant relationship between the level of SUA and OP.Conclusion. Thus, in postmenopausal women, the effect of SUA on the risk of OP was not revealed.